Modulation of dopamine and noradrenaline release and of intracellular Ca2+ concentration by presynaptic glutamate receptors in hippocampus - Malva, J. O. (1994)
1. We studied the release of [3H]-dopamine and [3H]-noradrenaline (NA) from hippocampal synaptosomes induced by glutamate receptors and the associated Ca2+ influx through Ca2+ channels. The release of tritiated neurotransmitters was studied by use of superfusion system and the intracellular free Ca2+ concentration ([Ca2+]i) was determined by a fluorimetric assay with Indo-1 as a probe for Ca2+. 2. Presynaptic glutamate receptor activation induced Ca(2+)-dependent release of [3H]-dopamine and [3H]-NA from rat hippocampal synaptosomes. Thus, L-glutamate induced the release of both neurotransmitters in a dose-dependent manner (EC50 = 5.62 microM), and the effect of 100 microM L-glutamate was inhibited by 83.8% in the presence of 10 microM 6-cyano-7-nitroquinoxaline-2,3-dioxine (CNQX), but was not affected by 1 microM (+)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]-cyclohepten-5,10-imine (MK-801). 3. Other glutamate receptor agonists also stimulated the Ca(2+)-dependent release of [3H]-dopamine and [3H]-NA as follows: N-methyl-D-aspartate (NMDA), at 200 microM, released 3.65 +/- 0.23% of the total 3H catecholamines, and this effect was inhibited by 81.2% in the presence of 1 microM MK-801; quisqualate (50 microM), S-alpha-amino-3-hydroxy-5-methyl-4-isoxazolopropionic acid (AMPA) (100 microM) or kainate (100 microM) released 1.57 +/- 0.26%, 1.93 +/- 0.17% and 2.09 +/- 0.22%, of the total 3H catecholamines, respectively. 4. The ionotropic glutamate receptor agonist, AMPA, induced an increase in the [Ca2+]i which was inhibited by 58.6% in the presence of 10 microM CNQX. In contrast, the increase in [Ca2+]i due to stimulation by glutamate was not sensitive to CNQX or MK-801.5. Nitrendipine, at I JAM, did not inhibit the neurotransmitter release induced by AMPA, but, both 0.5 micro M -conotoxin GVIA (w-CgTx) and 100 nM w-Aga IVA reduced catecholamine release to 49.03 +/- 3.79% and 46.06 +/- 10.51% of the control, respectively. In the presence of both toxins the release was reduced to 12.58 +/- 4.64% of the control.6. The results indicate that activation of presynaptic glutamate receptors of the NMDA and non-NMDA type induces the release of [3H]-dopamine and [H]-NA from rat hippocampal synaptosomes and that the release induced by AMPA involves the activation of N- and P-type Ca2" channels which allow the influx of Ca2" that triggers the 3H catecholamines release